Visionary Leadership Strategy in Implementing Vision and Mission Based on Education Reports at State Elementary School 14 Kayuagung - Efriyanti Efriyanti; Bukman Lian; Rohana Rohana (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2026)
This study aims to evaluate the impact of a principal’s visionary leadership strategy on school performance, specifically by examining the implementation of the school’s vision and mission through the lens of the Indonesian Education Report Card at SD Negeri 14 Kayuagung. A qualitative case study was conducted, employing document analysis of the 2024 Education Report Card data and strategic school planning documents to assess outcomes linked to leadership actions. The analysis focused on key performance indicators including literacy, numeracy, character, learning quality, and school safety climate. The implementation of visionary leadership, characterized by strategic planning, resource organization, and school-based management, correlated with a significant improvement of 6.66% in both literacy and numeracy indicators. Positive trends were also observed in character and learning quality. However, a slight decrease of 0.46% in the school safety climate indicator was identified, revealing a critical area of concern despite overall academic progress. The findings underscore the necessity for school principals to adopt integrated leadership strategies that not only drive academic and character development through a clear vision and collaborative management but also proactively monitor and strengthen the school’s safety and emotional climate to ensure holistic improvement. This study provides an empirical, data-driven examination of how visionary leadership operationalizes institutional vision into measurable outcomes within the specific framework of Indonesia's national Education Report Card. It contributes a nuanced understanding by highlighting that even within a successful leadership model, advancements in academic indicators can coincide with overlooked declines in school safety, offering a critical perspective for comprehensive school evaluation.